Framework for selecting assistive technology user-participation methods. Issue 2 (20th June 2016) - Draffan, E A; James, Abi; Wald, Mike; Idris, Amal
Abstract : Purpose: – A number of participatory research methodologies can be used to assist with developing assistive technologies. These methods vary in the amount that users lead and contribute to the work. Selecting the correct method can be important to ensure the overall success of the project and the engagement of users. The purpose of this paper is to explore factors that can impact on the degree of user participation. Design/methodology/approach: – The paper considers whether criteria, that might influence assistive technology (AT) selection made during an assessment of need, review or purchasing process, could also be used to clarify the appropriate strategies for user involvement when developing assistive technologies. It outlines how this approach has been applied to two research and development projects which aimed to improve AT provision within niche markets. Findings: – The paper demonstrates that it is possible to apply a decision making process to selecting the best participatory research method, based on factors affecting AT need. It reports on the outcomes of the user participation in the two research and development projects and discusses how this design approach has been applied to a third project. Originality/value: – By examining a possible framework for identifying appropriate user-participation approaches, this paper will aid those designing research and development AT projects, whilst encouraging user participation within similar projects.